Analysis of the Effect of Evaluation and Innovation in the Development of Construction Safety Culture on the Safety Leadership Model using SEM Approach - Taqwa, Fadhila Muhammad Libasut; Priyambodo, Bambang; Subkhan, Subkhan; Naibaho, Pio Ranap Tua (Universitas Ibn Khaldun, 2025)
In the construction sector, the Construction Safety Management System (SMKK) has been determined by the Regulation of the Minister of Public Works No. 10 of 2021 as a reference for addressing the risk of industrial accidents and improving building safety. Full implementation of occupational safety (K3) can minimize the risk of work accidents. However, in reality, there are still many obstacles for companies and employees, and many accidents in the workplace are caused by unsafe behavior factors by the workers themselves. The methodology used in this study involves various approaches, such as literature review and primary data acquisition through questionnaires targeting respondents in construction project environments. The collected data will be analyzed using the Structural Equation Modeling method to identify important variables. Data processing was performed using the Smart-PLS version 4.1.0.1 application to determine the outer and inner models. Hypothesis testing was conducted using bootstrapping, considering the Original Sample values, T-statistics, and P-values. Based on the results, it is concluded that safety leadership has a significant indirect influence on improving safety performance. The strengthening of leadership aspects has the largest impact on improving safety culture, which then influences the improvement of construction safety performance, with an original sample (O) value of 0.273, a sample mean (M) of 0.277, a standard deviation (STDEV) of 0.177, a T-statistic value of 2.324, and a P-value of 0.001. Furthermore, effective safety evaluation (e.g., constructive and systematic evaluation) can help build a stronger safety culture, which in turn will improve overall safety performance. The implementation of innovation in construction processes or safety technology can also encourage better safety behavior among workers, which then contributes to improved safety performance.